DEVELOPING A NOVEL COATED UREA WITH BIODEGRADABLE POLYMER AND UREASE INHIBITORS TO ENHANCE THE YIELD OF RICE GROWN UNDER AN USTIC TORRIFLUENT - S. K. Babar; Z. H. Shah; I. Rajpar; M. K. Yusop; S. Taban (Journal of Animal and Plant Sciences, 2022)
The study deals with evaluating the viability of using biodegradable polymer palm stearin (PS) as a coating material for the provision of nitrogen (N), copper (Cu), and zinc (Zn) on slow-release mechanism. Nitrogen in conventional form results mainly in ammonia volatilization loss. Decelerating hydrolysis rate of urea with the help of certain inhibitors (Cu and Zn); can enhance N-uptake and accordingly increases rice production. A novel PS coated urea was developed manually in laboratory conditions. The effect of PS coated urea evaluated for N, Cu and Zn concentration under field conditions on rice yield and nutrients concentration (N-Cu-Zn). The experiment made use of 140 kg N ha-1 coated with 10 and 15 kg Zn ha-1 and 3 and 5 kg Cu ha-1 applied separately or in combinations. Our results indicated that the applied polymer coated urea with 15 kg Zn ha-1 and 3 kg Cu ha-1 had affirmative response to increase the yield more than half as compared to control and one-fold increase in Zn and N contents in soil and plants (p ≤ 0.05). This study has prospective to apply Zn and Cu coated urea as environment friendly fertilizer to reduce the N-losses and increase Zn contents.
Keywords: ammonia volatilization; slow-release urea; synchronizing nutrients; alkaline soils